2020
DOI: 10.1186/s12920-020-00768-z
|View full text |Cite
|
Sign up to set email alerts
|

Integrative genomics analysis of various omics data and networks identify risk genes and variants vulnerable to childhood-onset asthma

Abstract: Background Childhood-onset asthma is highly affected by genetic components. In recent years, many genome-wide association studies (GWAS) have reported a large group of genetic variants and susceptible genes associated with asthma-related phenotypes including childhood-onset asthma. However, the regulatory mechanisms of these genetic variants for childhood-onset asthma susceptibility remain largely unknown. Methods In the current inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 85 publications
(88 reference statements)
0
21
0
Order By: Relevance
“…Studies have found TAP2 to be associated with various immune-related disorders, including autoimmune thyroiditis and type 1 diabetes [ 80 , 81 ], and pulmonary tuberculosis in Iranian populations [ 82 ]. Recently, Ma and colleagues [ 83 ] identified three cis-regulatory eSNPS for TAP2 as candidates for childhood-onset asthma risk (rs9267798, rs4148882 and rs241456). One of these (rs4148882) is present in the asthma GWAS data set used for our analysis ( FDR = 0.12) and is in weak LD with rs4148869 ( r 2 = 0.4).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have found TAP2 to be associated with various immune-related disorders, including autoimmune thyroiditis and type 1 diabetes [ 80 , 81 ], and pulmonary tuberculosis in Iranian populations [ 82 ]. Recently, Ma and colleagues [ 83 ] identified three cis-regulatory eSNPS for TAP2 as candidates for childhood-onset asthma risk (rs9267798, rs4148882 and rs241456). One of these (rs4148882) is present in the asthma GWAS data set used for our analysis ( FDR = 0.12) and is in weak LD with rs4148869 ( r 2 = 0.4).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have found TAP2 to be associated with various immune-related disorders, including autoimmune thyroiditis and type 1 diabetes 75,76 , and pulmonary tuberculosis in Iranian populations 77 . Recently, Ma and colleagues 78 identified three cis-regulatory eSNPS for TAP2 as candidates for childhood-onset asthma risk (rs9267798, rs4148882 and rs241456). One of these (rs4148882) is present in the asthma GWAS data set used for our analysis ( FDR = 0.12) and is in weak LD with rs4148869 ( r 2 = 0.4).…”
Section: Resultsmentioning
confidence: 99%
“…To highlight the functional risk genes whose expressions were significantly associated with PBC, we leveraged both S-PrediXcan 26 and S-MultiXcan 27 to combine GWAS summary statistics on PBC with GTEx eQTL data 28 (Supplemental Methods S5). Furthermore, We referenced the method used in previous studies 11,24,29,30 to perform an in silico permutation analysis of 100,000 times of random selections (N Total ) for validating the consistency of results from S-MultiXcan analysis with other results from three distinct analyses: MAGMA analysis, and S-PrediXcan on liver and blood (Supplemental Methods S6). We also performed a gene-property analysis using the FUMA tool 31 to integrate gene-level association signals from GWAS summary statistics on PBC with scRNA-seq data based on liver tissue from the Mouse Cell Atlas 32 .…”
Section: Methodsmentioning
confidence: 99%